Diagnosis and treatment for anal fistula: a systematic review of clinical practice guidelines and consensus statements - Lu, Min-Yuan; Wang, Jing; Wang, Zhao-Chu; Cai, Zhao-Lian; Liang, Ning; Shi, Rong (Frontiers in Surgery, 2025)
BackgroundAnal fistula constitutes a pathological channel originating either from the anal canal or rectum to the skin surrounding the anus, primarily characterized by recurrent pain, purulent discharge, and pruritus. This study aims to compare and standardize the recommendations for the diagnosis and treatment of anal fistula, drawing on contemporary clinical practice guidelines.MethodsA comprehensive search was conducted across multiple databases including PubMed, EMBASE, China National Knowledge Infrastructure, Wanfang Database, Chinese Science and Technology Periodical Database, and Chinese Biological Medicine Database, from their inception through April 1, 2024. The objective was to collate all published guidelines on anal fistula. The quality of the eligible guidelines was appraised by two reviewers using the Appraisal of Guidelines for Research and Evaluation II instrument.ResultsThe search yielded fifteen guidance documents —comprising nine guidelines and six consensus statements —each offering specific recommendations. Twelve of these documents address screening and diagnosis of anal fistula, while all fifteen discuss various treatment and management strategies. Document analysis highlighted MRI as the predominant diagnostic recommendation. Treatment and management strategies were categorized into four categories: preoperative management, surgical method selection, pharmacological interventions, and postoperative management. Regarding surgical interventions, all guidelines address incision and drainage of fistulas. Most guidelines offer a low recommendation for cutting setons, mainly attributed to the presence of incontinence. For high–positioned anal fistula, a push-pull flap procedure is recommended, whereas the LIFT procedure is advocated for newly identified, high, and sphincter-penetrating fistulas. Among the 15 guidelines and consensus statements evaluated in this study, more than half demonstrated methodological limitations, with particularly deficient performance in the applicability domain. As a critical determinant of implementation effectiveness, these deficiencies may undermine guidelines' capacity to optimize health outcomes.ConclusionThere is a pressing need for an updated search of potential evidence on the diagnosis and treatment of anal fistula. Effective diagnoses and therapeutic approaches, whether conventional or complementary and alternative medicine, should be thoroughly evaluated and incorporated based on robust evidence.